Influence of focused-ion-beam microfabrication on superconducting transition in exfoliated thin films of layered superconductor NbSe2. (September 2019) - Tomori, Hikari; Hoshi, Naoki; Inoue, Dai; Kanda, Akinobu
Abstract: We have experimentally studied the influence of the focused ion beam (FIB) microfabrication on the superconducting properties of exfoliated thin films of layered superconductor NbSe2 through transport measurement. We observed significant decrease of the residual-resistance ratio (RRR), indicating the formation of defects by the FIB. Although clear superconducting transition was seen before the FIB microfabrication, after FIB it was blurred, and one sample exhibited insulating behavior. The possible origins of the changes in the superconducting properties are discussed.